Asociación entre estigma y adherencia al tratamiento antituberculoso en adultos en establecimientos de primer nivel de Iquitos en 2025 - Tuesta Bardales, Bruno Leandro (2025)
Objective: To determine the association between tuberculosis-related stigma and treatment adherence in adult patients treated at primary healthcare centers in Iquitos during 2025. Methods: Observational, analytical, cross sectional and prospective study. Adult patients diagnosed with tuberculosis and undergoing treatment were included, selected through stratified proportional random sampling. Two validated instruments were used: the Tuberculosis Stigma Scale (adapted to the Peruvian context) and the Morisky Green adherence questionnaire. Sociodemographic data were also collected. Statistical analysis was performed using SPSS, including frequencies, association tests (Chi-square or Fisher’s exact test), and prevalence ratios with 95% confidence intervals. A p-value < 0.05 was considered statistically significant. Results: Most participants were male, single or cohabiting, and had completed secondary education. A total of 75.6% reported a low level of stigma, and 62.5% demonstrated adequate treatment adherence. No statistically significant association was found between stigma and adherence. Likewise, no associations were found with sociodemographic variables, except for age group, with adults showing lower levels of stigma (p = 0.029), although relevant clinical trends were observed. Conclusions: Although no statistically significant association was found between stigma and adherence, a trend suggests a potential negative impact. Further longitudinal studies with larger samples are recommended. The findings provide valuable local evidence to guide patient-centered intervention strategies.